STUDY OF THE INFLUENCE OF VARIOUS METHODS OF FUEL INPUT THROUGH BURNERS ON COMBUSTION PROCESSES - Askarova, A.S.; Bolegenova, S.A.; Nugymanova, A.O.; Maximov, V.Yu.; Bolegenova, S.A.; Ospanova, Sh.S.; Shortanbayeva, Zh.K.; Aubakirov, N.P.; Nurmukhanova, A.Z. (Eurasian Physical Technical Journal, 2025)
This paper presents new results of computational experiments to study the influence of various methods of fuel input (straight flow and vortex with a flow deflection angle of the pulverized coal stream) across the firing systems on combustion processes utilizing the BKZ-75 boiler combustion chamber case of the Shakhtinskaya TPP (Kazakhstan), fluidized combusting Karaganda coal with high ash content. According to the results of computational combustion modeling, the following results were derived: the total velocity vector distributions, spatial distributions of temperature, and concentrations of carbon oxides and nitrogen dioxide (NO₂) within the full volume through the combustion zone and at the chamber’s discharge. It has been appeared that the vortex strategy of providing the discuss blend makes it conceivable to enhance the method in the combustion of high-ash coal, as in this case there’s an increment in temperature within the center of the burn and a lower temperature observed at the combustion zone outlet, which features a noteworthy effect on the chemical forms of the arrangement of reaction products formed during combustion. When employing vortex burner devices, the concentration levels at the combustion outlet zone for carbon monoxide (CO) decrease by about 15 %, and for nitrogen dioxide (NO2) by roughly 20 % relative to direct‑flow burner devices. The comes about gotten make it conceivable to create proposals for the advancement of ideal strategies for managing flame structure and combustion dynamics of a pulverized coal burn to extend the productivity of vitality offices and decrease emanations of hurtful substances into the environment.